Spatio‐temporal variation of gross CO2 and CH4 diffusive emissions from Australian reservoirs and natural aquatic ecosystems, and estimation of net reservoir emissions. Issue 2 (19th June 2013) - Bastien, Julie; Demarty, Maud
Abstract Carbon dioxide (CO2) and methane (CH4) diffusive emissions were measured during two field surveys in Queensland and Tasmania, Australia, using the floating chamber method. Bubbling and degassing emissions in 2010 were estimated in Koombooloomba Dam reservoir using only inverted funnels and gas concentrations, respectively. A total of 14 reservoirs and 16 rivers and lakes were sampled from 2006 to 2010. Spatial variation was substantial within each water body, as well as between them. The main drivers of diffusive emission variation were physiographic region and climate, with a clear demarcation being observed between diffusive emissions from tropical Queensland and temperate Tasmania, and between the humid West Coast Range (Tasmania) and dry Central Plateau (Tasmania). Higher CO2 and CH4 diffusive emissions were observed during the dry season, when long water residence times would promote organic matter degradation. Estimated total gross emissions, including diffusive, bubbling and degassing emissions, for Koombooloomba Dam reservoir were about 1.5 × 106t CO2eq km2 per year, or 24 × 106 t CO2eq per year. This corresponds to a plant emission factor of 3.18 kg CO2eq MWh−1. Using an estimate of terrestrial emissions derived from literature data for the Tully River catchment area, rough estimated net emissions from the catchment area are about 44 kt CO2eq per year, or 5.83 kg CO2eq MWh−1, which is in the lower range of the studied reservoirs.